The masculinization of domestic cooking: a historical study of Swedish cookbooks for men. Issue 4 (2nd October 2022) - Andersson, Helen; Eriksson, Göran
ABSTRACT: This study analyzes how men's domestic cooking is represented and masculinized in cookbooks, written by men for men and published in 1975, 1992, and 2010, respectively. Departing from the concept of domestic masculinities, it uses the methods of Multimodal Critical Discourse Analysis. It asks: what kind of values and ideas connected to men, food, and the home are realized in texts and images? And how are these legitimized and naturalized? As the study's context is Sweden, a country known for its pursuit of gender equality, the study focuses on how men's domestic cooking has been represented in cookbooks published roughly 20 years apart. The analysis shows that, while the first two books are characterized by a 'real man' discourse and working-class masculinity, the 2010 book represents a masculinity in line with a 'new man image' closely linked to consumption and materiality. However, structurally, there are few differences. Values associated with traditional middle-class masculinities, traditional gender norms, and gendered division of domestic labor are reproduced. Men's cooking is recontextualized as a playful leisure activity. In all three books, cooking becomes another way for a man to appear successful – both in relation to other men and women, and in socioeconomic terms.